Whole-genome sequencing of Shigella for surveillance purposes shows (inter)national relatedness and multidrug resistance in isolates from men who have sex with men. Issue 4 (6th April 2023) - van den Beld, Maaike; Pijnacker, Roan; van Dam, Alje; Bovée, Lian; Kwa, David; Linde, Ineke; Wolthuis, Roxanne; Notermans, Daan; Bosch, Thijs; Franz, Eelco
Abstract : In the Netherlands, more than half of domestic shigellosis cases are among men who have sex with men (MSM), particularly in the Amsterdam region. However, there is limited insight into which Shigella strains circulate in the Netherlands. Our objective was to assess the added value of whole-genome sequencing (WGS)-based surveillance for Shigella . To this end, we determined the relatedness among Shigella spp. isolates from patients in the Amsterdam region, as well as in an international context, including antimicrobial resistance markers, using WGS. The following criteria were used: it should provide insight into (1) clustering of shigellosis cases and the affected population, (2) the extent of admixture of MSM-associated isolates with those from the broader population and (3) the presence of antimicrobial resistance. It should then lead to more opportunities for targeted control measures. For this study, Shigella isolates from three laboratories in the Amsterdam region obtained between February 2019 and October 2021 were subjected to Illumina WGS at the National Institute for Public Health and the Environment (RIVM). Raw data were quality-checked and assembled, the Shigella serotype was determined with ShigaTyper, and antimicrobial resistance markers were detected using ResFinder and PointFinder. For Shigella sonnei, subclades were determined using Mykrobe. Relatedness of isolates, including 21 international reference genomes, was assessed with core genome multilocus sequence typing. In total, 109 isolates were included, of which 27 were from females (25 %) and 66 were from males (61 %), with which the majority ( n =48, 73 %) being from MSM. No information on sex was available for the remaining 16 cases. The WGS data for all isolates, comprising 55  S . sonnei, 52  Shigella flexneri, 1  Shigella boydii and 1  Shigella dysenteriae, met the quality criteria. In total, 14 clusters containing 51 isolates (49 %) were identified, with a median cluster size of 2.5 cases (range: 2–15). Nine out of 14 clusters were MSM-associated, and 8 clusters (57 %) were travel-related. Six of the MSM clusters were related to international reference genomes. The prevalence of antimicrobial resistance markers was higher among isolates from MSM than non-MSM patients, particularly for ciprofloxacin (89 vs 33 %) and azithromycin (58 vs 17 %). In conclusion, about half of Shigella spp. patients were part of a cluster, of which a substantial part were related to international reference genomes, particularly among MSM, and a high prevalence of antimicrobial resistance markers was found. These findings indicate widespread international circulation of Shigella spp., particularly among MSM, with multidrug resistance that hampers treatment of patients. Moreover, the results of this study led to the implementation of a national WGS-based laboratory surveillance programme for Shigella spp. that started in April 2022.